Failure of surgical treatment in methamphetamine body-stuffers. (May 2015) - Bahrami-Motlagh, Hooman; Hassanian-Moghaddam, Hossein; Behnam, Behdad; Arab-Ahmadi, Mehran
Abstract: Body stuffing is defined as ingestion of unpackaged or packaged illicit drugs in a quick process. The drugs have usually been wrapped loosely in cellophane, plastic bags, paper, or aluminum foil. Methamphetamine toxicity is a dangerous state that occurs during methamphetamine leakage from the ingested packages in the gastrointestinal tract. This is usually occurring with cocaine and heroin, but methamphetamine body stuffing may less commonly happen, as well. Accordingly, management of methamphetamine body-stuffers is an important subject that has remained a controversy in clinical and legal aspects. We have reported two body-stuffer cases who underwent exploratory laparotomy. Although surgery was done, it was not useful to exit packs and even led to severe methamphetamine toxicity. These cases show that surgical treatment may be ineffective and even harmful in body-stuffers. On the other hand, this report suggests that pre and post-operation abdominal CT-scan is necessary for evaluating surgical treatment in patients who are still symptomatic. Highlights: Treating methamphetamine body stuffers in an emergency department is challenging. The optimal management for body stuffers has not been formally determined. Radiologic findings are still important to improve accuracy of diagnosis. Drug packs are small in size and may be ignored during the operation. Surgery techniques may accelerate drug release and exaggerate meth toxicity leading to death.